Genomic elements located in the accessory repertoire drive the adaptation to biocides in Listeria monocytogenes strains from different ecological niches. (September 2022) - Palma, Federica; Radomski, Nicolas; Guérin, Alizée; Sévellec, Yann; Félix, Benjamin; Bridier, Arnaud; Soumet, Christophe; Roussel, Sophie; Guillier, Laurent
Abstract: In response to the massive use of biocides for controlling Listeria monocytogenes (hereafter Lm ) contaminations along the food chain, strains showing biocide tolerance emerged. Here, accessory genomic elements were associated with biocide tolerance through pangenome-wide associations performed on 197 Lm strains from different lineages, ecological, geographical and temporal origins. Mobile elements, including prophage-related loci, the Tn 6188_qacH transposon and pLMST6_ emrC plasmid, were widespread across lineage I and II food strains and associated with tolerance to benzalkonium-chloride (BC), a quaternary ammonium compound (QAC) widely used in food processing. The pLMST6_ emrC was also associated with tolerance to another QAC, the didecyldimethylammonium-chloride, displaying a pleiotropic effect. While no associations were detected for chemically reactive biocides (alcohols and chlorines), genes encoding for cell-surface proteins were associated with BC or polymeric biguanide tolerance. The latter was restricted to lineage I strains from animal and the environment. In conclusion, different genetic markers, with polygenic nature or not, appear to have driven the Lm adaptation to biocide, especially in food strains but also from animal and the environment. These markers could aid to monitor and predict the spread of biocide tolerant Lm genotypes across different ecological niches, finally reducing the risk of such strains in food industrial settings. Highlights: Several signals of biocide-adaptation are located in the accessory repertoire. Most of the associations with biocide tolerance involves mobile genetic elements. Recombination-aware pangenome-wide association study reveals strong associations. Genome-wide significances differ from Bonferroni to quantile-quantile approach.